2001
DOI: 10.1103/physrevd.64.034005
|View full text |Cite
|
Sign up to set email alerts
|

Lattice regularization for chiral perturbation theory

Abstract: The SU(3) chiral Lagrangian for the lightest octets of mesons and baryons is constructed on a spacetime lattice. The lattice spacing acts as an ultraviolet momentum cutoff which appears directly in the Lagrangian so chiral symmetry remains explicit. As the lattice spacing vanishes, Feynman loop diagrams typically become divergent due to inverse powers of the lattice spacing, and these divergences get absorbed into counterterms such that the standard results of dimensional regularization are obtained. One advan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…For example, we have shown that the same physics results from use of lattice size as a regulator [16]. The purpose of the cutoff function is to remove the model-dependent short distance portions of the loop integrals which are not suppressed in dim reg.…”
Section: Introductionmentioning
confidence: 89%
“…For example, we have shown that the same physics results from use of lattice size as a regulator [16]. The purpose of the cutoff function is to remove the model-dependent short distance portions of the loop integrals which are not suppressed in dim reg.…”
Section: Introductionmentioning
confidence: 89%
“…In Ref. [115] a lattice regularized version of ChPT is used to determine the typical size of discretization errors. For physical values of m q , baryon masses turn out to be essentially independent of lattice spacing when π/a Λ χ .…”
Section: Brief Survey Of Lattice Qcd Resultsmentioning
confidence: 99%
“…We end this section with a number of remarks: 14 Our normalization is such that in the real world f π = 130.4 MeV. Another common convention uses a value smaller by a factor √ 2.…”
Section: Conserved Currentsmentioning
confidence: 99%
“…It therefore describes all pion physics to leading order in pion momenta. For example, writing φ as φ = φ a T a , with T a the generators of SU(3) obeying 14) one finds the leading-order prediction for the pion scattering amplitude from a tree-level calculation using Eq. (2.13):…”
mentioning
confidence: 99%